DYNAMICS OF INDICATORS OF COORDINATION ABILITIES OF BASKETBALL PLAYERS OF PRIMARY TRAINING GROUPS UNDER THE INFLUENCE OF USING SPECIAL PREPARATORY EXERCISES - Yuri Gorchanyuk; Maxim Merzlikin; Tamara Lyakhova (Kharkiv State Academy of Physical Culture, 2021)
Purpose: to determine the degree of influence of special preparatory exercises on indicators of coordination abilities of basketball players of initial preparation groups. Material and methods: the study involved 40 athletes aged 9 - 11 years, that are part of initial training groups of the second year of study in the sports school № 7 in Kharkiv (control group 20 athletes, experimental group 20 athletes). To establish the indicators of coordination readiness of young basketball players, the standard test exercises proposed by L.P. Sergienko [13] were used. Results: in the training process of the experimental group of special - preparatory exercises were used: various jumps and acrobatic exercises, as well as sets of exercises on a trampoline. This technique had a positive effect on the coordination abilities of basketball players in the initial training group, and significant differences were found between the results before and after the pedagogical experiment (p<0,05). Conclusions: the positive dynamics of coordination abilities indicators of the experimental group is established after the pedagogical experiment. Thus, in testing the control of evaluation and regulation of spatio-temporal and dynamic parameters of movements, the improvement of results in percentage was from 9 % to 43 %, in testing the evaluation of sense of time the increase in results ranged from 27% to 56%, improvement of muscle accuracy efforts ranged from 3 % to 16 %, the dynamics of indicators of control of spatial orientation was from 7 % to 43 %, the results of control of stability of static and dynamic balance after the pedagogical experiment improved from 14% to 18%, indicators of sense of rhythm changed by 7 %, indicators of control of the ability to arbitrarily relax muscles improved by 3 %, the results of control of coordination of movements were increased by 31 % (p>0,05).